DAMPAK PENGGUNAAN METODE KONTRASEPSI VASEKTOMI TERHADAP KESEHATAN DAN KEHARMONISAN PADA PASANGAN SUAMI ISTRI DI KECAMATAN PAGERBARANG KABUPATEN TEGAL TAHUN 2016 - Reni Mulyanti; Suyatno Suyatno; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Vasectomy is a contraceptive method most low demand. Factors that can affect a man to choose the contraceptive is side effects from the health and psychological that can affect the harmony. According to data from KB in District Pagerbarang 2015, the number of participants vasectomy as much as 1.12%, the number is still very small compared with other contraceptives. The purpose of this study was to determine the impact of differences in the health and harmony of the couple before and after using a vasectomy contraceptive method. This research is explanatory with cross sectional approach. The sample in this study is most couples whose husband used a vasectomy contraceptive method. Determining of the samples in this study by Lemeshow formula calculations as many as 47 people. The sampling technique using proportional random sampling method. Descriptive analysis is used to describe the health variables husband and statistical analysis were used to analyze differences in the health effects and the impact of harmony wives married couples. The analytical method used is the Wilcoxon test. Husband health variables descriptively showed that respondents felt their health complaints such as pain in the scar of vasectomy (2.1%), bruises on the former vasectomy (2.1%), fever after vasectomy (2.1%), swelling on the scrotum (2.1%), and swelling of the skin that protects the testicles (4.3%). Statistical analysis showed no differences in the health impact on his wife with a p-value of 0.001 and showed an increase in the average value, it means that a husband who uses a vasectomy, the mother's health is getting better. There are differences in the impact of harmony in couples with a p-value of 0.001 and showed a decrease in the average value, meaning that a husband who uses a vasectomy, the harmony of the couple getting lower.